Study on the Immunogenicity of Infectious Bursal Disease Virus VP2 proteins Expressed in Silkworm - YU Lian; SONG Kun-hua; ZHANG Yao-zhou; HUANG Yao-wei; LI Jian-rong (浙江大学学报. 农业与生命科学版, 2000)
The VP2 protein of infectious bursal disease virus (IBDV) was expressed in spring and autumn silkworm larvae as detected by Western blot and ELISA. Non-immunized 18-day-old chickens were vaccinated via subcutaneous injection with a vaccine preparation made from the lymph of spring silkworms containing VP2 expression product. The boosting immunization was carried out two weeks later. The lymph of autumn silkworms was freeze-dried as the oral vaccine. Non-immunized 18-day-old chickens were fed on the oral vaccine every other day. Serum samples from the immunized chickens were harvested. Virus neutralization (VN) test showed that the titers of VN antibody was 1∶4211.4 in the sera of chickens receiving subcutaneous immunization and 1∶3118.9 in those of chickens fed on oral vaccine at day 37 post-immunization. The immunized chickens were challenged with BC6/85, a reference Chinese virulent IBDV strain at the 37th day after vaccination. The rate of protection against BC6/85 infection was 100% for the chickens with subcutaneous vaccination and 80% for those receiving oral vaccine. These results indicate that the VP2 protein expressed in silkworm larvae is immunogenic and the established expression system for VP2 has laid a firm basis for the development of practical yet low-cost vaccines against infectious bursal disease.